Gray matter volumetric study of major depression and suicidal behavior. (30th January 2019) - Rizk, Mina M.; Rubin-Falcone, Harry; Lin, Xuejing; Keilp, John G.; Miller, Jeffrey M.; Milak, Matthew S.; Sublette, M. Elizabeth; Oquendo, Maria A.; Ogden, R. Todd; Abdelfadeel, Nashaat A.; Abdelhameed, Mohamed A.; Mann, J. John
Highlights: Risk for suicidal behavior has been linked to structural brain deficits. Suicidal behavior is heterogeneous in terms of suicidal act's lethality. Higher-lethality suicidal behavior may be associated with larger prefrontal cortex. Abstract: Structural brain deficits are linked to risk for suicidal behavior. However, there is disagreement about the nature of these deficits, probably due to the heterogeneity of suicidal behavior in terms of the suicidal act's lethality. We hypothesized that individuals with major depressive disorder (MDD) and history of more lethal suicide attempts would have lower gray matter volume (GMV) of the prefrontal regions and insula compared with MDD lower-lethality attempters and MDD non-attempters. We collected structural MRI scans on 91 individuals with MDD; 11 with history of higher-lethality suicide attempts, 14 with lower-lethality attempts, and 66 were non-attempters. Differences in GMV between these three groups were examined using both regions-of-interest (ROI) and brain-wide voxel-based morphometry (VBM) analyses. Both ROI and VBM analyses showed that higher-lethality suicide attempters have greater GMV of the prefrontal cortical regions and insula, compared with the other two groups. Although this contrasts with our hypothesis, the observed larger prefrontal cortex GMV in higher-lethality suicide attempters may underlie the set of attributes observed previously in this suicidal subgroup, including enhanced suicide attempt planning, greater response inhibition, and delayed reward capabilities. Future studies should further examine the role of these brain regions in relation to suicidal intent and planning.